SUBSTANTIATION OF A SAFE PERIOD OF TIME FOR THE ORAL CAVITY SANITATION UNDER GENERAL ANESTHESIA IN CHILDREN AGED 12-18 YEARS - Koval, О.І. (World of Medicine and Biology, 2020)
The article substantiates a safe period of time for the sanitation of the oral cavity in an outpatient setting under general anesthesia in children aged 12-18 years in order to prevent the occurrence of cognitive dysfunction of the brain against the background of hypoxic lesions. The results of the study revealed: іn order to prevent the occurrence of brain hypoxia during dental sanitation of the oral cavity in conditions of general anesthesia (without intubation), children aged 12 to 18 years should spend within 60±15 minutes; the contraindication for the planned sanitation of the oral cavity in conditions of general anesthesia (without intubation) is the absence of a history of acute respiratory diseases for at least 2 weeks; іf there is a history of acute respiratory disease in less than 2 weeks and an acute dental need, ambulance in general anesthetic conditions (without intubation) is possible within ≤20 min.
Keywords: cerebral oximetry; SpO2; rSO2; general anesthesia